(untitled) - Welsh, Matt (Paris, 1995)
Linux is and how to use it. If you like the idea of having additional security and stability in your system, you should start learning more about this revolutionary operating system by using sites that provide Linux links. This book contains information on the Linux Operating System, especially for beginners. Programmers and system administrators can also easily benefit from the discussions inside.
Keywords: Linux (tệp máy tính),Linux (Computer file)